Multibeam bathymetry raw data (Kongsberg EM122 entire dataset) of RV MARIA S. MERIAN during cruise MSM111 - Dorschel, Boris; Streuff, Katharina Teresa; D'Mello, Gavin; Dreutter, Simon; Kucera, Michal (PANGAEA, 2023)
Multibeam data were collected with RV Maria S. Merian along the route of cruise MSM111 and data acquisition was continuously monitored during the survey. Multibeam sonar system was Kongsberg EM122. SVPs were retrieved from CTD data from other working groups on board. SVPs were processed with HydrOffice SoundSpeedManager (https://www.hydroffice.org/soundspeed/main) and extended with World Ocean Atlas 13 (https://doi.org/10.7289/v5f769gt). SVP data were applied during acquisition. Multibeam data are unprocessed and may contain outliers and blunders and should not be used for grid calculations and charting projects without further editing. The raw multibeam sonar data in Kongsberg multibeam processing format (.all) were recorded with Kongsberg SIS. Raw data files can be processed using software packages like CARIS HIPS/SIPS or MB-System. For updated vessel configuration file check further details.